A new retrogressive thaw slump (RTS) inventory in central Qinghai-Tibet Plateau ... - Dongdong, Yang; Haijun, Qiu; Bingfeng, Ye; Ya, Liu; Juanjuan, Zhang; Yaru, Zhu (Zenodo, 2023)
A new retrogressive thaw slump (RTS) inventory in central Qinghai–Tibet Plateau (QTP) were generated based on visual interpretation of nine satellite images (WV-2, Google Earth image, Ziyuan-3, Gaofen-2, Gaofen-1) and field investigations. A total 459 RTSs were confirmed with an accumulative area of 1199.49 ha (in time slice of 2020). To reduce the uncertainty in identifying the RTS boundaries, all of the images were spatially corrected based on a reference image, which was obtained on 29 December 2015. The RTS inventory published by Luo et al., (2022) and Xia et al., (2022) were refered when we conduct visual interpretation. ... : {"references": ["Luo, J., Niu, F., Lin, Z., Liu, M., Yin, G., & Gao, Z. (2022). Inventory and frequency of retrogressive thaw slumps in permafrost region of the Qinghai\u2013Tibet Plateau. Geophysical Research Letters, 49(23), e2022GL099829. doi.org/10.1029/2022GL099829", "Xia, Z., Huang, L., Fan, C., Jia, S., Lin, Z., Liu, L., ... & Zhang, T. (2022). Retrogressive thaw slumps along the Qinghai\u2013Tibet Engineering Corridor: a comprehensive inventory and their distribution characteristics. Earth System Science Data, 14(9), 3875-3887."]} ...